On the relationship between blend state and dispersibility of adhesive mixtures containing active pharmaceutical ingredients - Jonas Rudén; Göran Frenning; Tobias Bramer; Kyrre Thalberg; Göran Alderborn (Elsevier, 2021)
The objectives of this investigation were to study the evolution in blend state of adhesive mixtures containing the active pharmaceutical ingredients (APIs) salbutamol, budesonide and AZD5423 and to study the relationship between blend state and dispersibility of the mixtures, as assessed by the fine particle fraction (FPF). A series of adhesive mixtures of varied fines concentration were prepared for each API using the same type of carrier. Based on visual examination and powder mechanics, blend states were identified and summarized as blend state maps for each API. The dispersibility of the mixtures was studied using a Fast Screening Impactor (FSI) equipped with a ScreenHaler. The evolution in blend state differed between the APIs in terms of the width of the blend states. The structure of the adhesion layer also differed between the APIs, from relatively uniform to a heterogeneous layer with small agglomerates dispersed on the carrier surface. All three APIs expressed a similar type of bended relationship between FPF and fines concentration. However, the initial rate of increase and the fines concentration of the plateau differed between the APIs. The adhesive mixtures of all APIs followed the three main states in terms of structural evolution and the overall shape of the FPF-fines concentration profiles could be explained by the evolution in blend state. It is proposed that the structure of the adhesion layer is an important factor explaining the differences in blend state - blend dispersibility relationships between the APIs.